2021
DOI: 10.1186/s12974-021-02080-8
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule antagonist of VLA-4 (GW559090) attenuated neuro-inflammation by targeting Th17 cell trafficking across the blood-retinal barrier in experimental autoimmune uveitis

Abstract: Background The integrin VLA-4 (α4β1) plays an important role in leukocyte trafficking. This study investigated the efficacy of a novel topical α4β1 integrin inhibitor (GW559090, GW) in a mouse model for non-infectious posterior uveitis (experimental autoimmune uveitis; EAU) and its effect on intraocular leukocyte subsets. Methods Mice (female; B10.RIII or C57Bl/6; aged 6–8 weeks) were immunized with specific interphotoreceptor retinoid-binding prot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…The expression of VLA-4 (α4β1 integrin), the ligand to VCAM-1, has been reported mostly in non-CD4 + T cells and rarely (2%) on uveitogenic CD4 + T cells during the early stages of EAU in C57BL/6 mice [ 28 ]. Our data demonstrated that at peak classical EAU in B10.RIII mice, there was an equal expression (30~40%) of VLA-4 by both Th1 and Th17 cells [ 35 ]. The increase in VLA-4 expression by CD4 + T cells was confined to the draining lymph nodes and the eye, but not the peripheral blood, suggesting that pathogenic leukocytes expressing VLA-4 are only present at local sites of inflammation [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of VLA-4 (α4β1 integrin), the ligand to VCAM-1, has been reported mostly in non-CD4 + T cells and rarely (2%) on uveitogenic CD4 + T cells during the early stages of EAU in C57BL/6 mice [ 28 ]. Our data demonstrated that at peak classical EAU in B10.RIII mice, there was an equal expression (30~40%) of VLA-4 by both Th1 and Th17 cells [ 35 ]. The increase in VLA-4 expression by CD4 + T cells was confined to the draining lymph nodes and the eye, but not the peripheral blood, suggesting that pathogenic leukocytes expressing VLA-4 are only present at local sites of inflammation [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our data demonstrated that at peak classical EAU in B10.RIII mice, there was an equal expression (30~40%) of VLA-4 by both Th1 and Th17 cells [ 35 ]. The increase in VLA-4 expression by CD4 + T cells was confined to the draining lymph nodes and the eye, but not the peripheral blood, suggesting that pathogenic leukocytes expressing VLA-4 are only present at local sites of inflammation [ 35 , 36 ]. This is supported by an in vitro study showing that antibody to VCAM-1 does not affect activated non-uveitogenic Th1 and Th17 cell migration [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microglia have been shown to be essential for inducing the retinal inflammatory response in experimental autoimmune uveitis (EAU) [150]. EAU is a T cell-mediated mouse model of chorioretinitis whereby inflammation is induced by immunization with retinal antigens [153].…”
Section: Posterior Uveitismentioning
confidence: 99%
“…in the retina both perivascularly and in tertiary lymphoid clusters [154,160]. When EAU mice were given an inhibitor to integrin VLA-4, an adhesion molecule implicated in CD4+ T cell recruitment, fewer Th17+ subset of T cells and Ly6C+ monocyte/macrophages crossed the BRB, resulting in reduced clinical disease severity [153]. Repeated exposure to systemic LPS also led to BRB breakdown, retinal microglia proliferation and activation, and macrophage infiltration [161].…”
Section: Posterior Uveitismentioning
confidence: 99%